Model Policy for Research Data Management (RDM) at Research Institutions/Institutes - (:unkn) unknown (My University, 2017)
Modelo de política de Gestión de Datos de Investigación (GDI)
LEARN Project
Keywords: Datos de investigación; Gestión de datos